FTIR analysis of silica fume and iron dust added concrete. (2022) - Jain, Bhupesh; Sancheti, Gaurav; Jain, Vaibhav
Abstract: Due to rapid industrialization, India is facing from developing to developed country. For that industries are growing at a very fast rate. As a result, large amount of waste is generated. The disposal of this waste material is a big problem. In this investigation, industrial waste such as Iron Dust (ID) and Silica Fume (SF) are used in place of fine aggregate and cement respectively in concrete. Fourier Transform Infrared (FTIR) spectroscopy is used to identify different phases of hydration product. Bands observed in FTIR spectra were compared with standard results and change in the spectra was observed. Results obtained from FTIR analysis were compared with compressive strength and optimum results were found. The optimum results were obtained for mix in which 10% cement and 20% fine aggregate were replaced with the silica fume and iron dust respectively.